Histopathological composition of thrombus material in a large cohort of patients with acute ischemic stroke: a study of atypical clots - Rojas-Bartolomé, Laura; Payá, María; Barbella-Aponte, Rosa; Restrepo Carvajal, Laura; García-García, Jorge; Ayo-Martín, Oscar; Molina-Nuevo, Juan David; Serrano-Heras, Gemma; Juliá-Molla, Enrique; Pedrosa-Jiménez, María José; López-Martínez, Lorena; Fernández López, Ángela; et al. (Frontiers in Neurology, 2025)
IntroductionClot composition appears to be associated with outcomes in stroke recanalization therapy. This study aims to analyze thrombus composition and assess the relationship between atypical clot composition and clinical parameters, laboratory markers, and recanalization strategies in a series of patients with acute ischemic stroke (AIS) undergoing endovascular treatment (EVT).MethodsThis is a prospective single-center registry conducted from December 2014 to July 2022. All retrieved clots were examined under an established protocol and classified as follows: red blood cell-rich clots (RBC), fibrin/platelet-rich clots (FPC), mixed clots (MC), septic emboli (SE), atheroma emboli (AE), fatty emboli (FE), and calcium emboli (CE). We categorized them into two groups: atypical clot composition (ACC: SE, AE, FE, and CE) and usual clot composition (UCC: RBC, FPC, and MC). A subgroup of 10 ACC (four SE, three AE, two FE, and one CE) and nine UCC (three RBC, three FPC, and three MC), matched by age and sex, was analyzed using immunohistochemistry to detect neutrophil extracellular traps (NETs).ResultsA total of 606 patients were assessed for EVT, with 448 (73.92%) meeting the inclusion criteria. The clot categorization was as follows: FPC 211 (47.1%), RBC 105 (23.4%), MC 104 (23.2%), SE 16 (3.6%), AE 5 (1.1%), CE 4 (0.9%), and FE 3 (0.7%). Consequently, we classified 420 (93.75%) patients into the UCC group and 28 (6.25%) into the ACC group. Bivariate analysis revealed that the ACC group had a significantly higher number of leukocytes (11.40 leukocytes/mm3 vs. 9.49, p = 0.005), a greater frequency of TICA occlusion (28.6% vs. 9.8%, p = 0.006), and higher mortality at three months (28.6% vs. 12.4%, p = 0.038). Multivariate analysis indicated that atypical clot composition was significantly associated with a higher prevalence of diabetes mellitus, smoking, occlusion of the terminal internal carotid artery, and an increased number of passes. Immunohistochemical studies showed the presence of neutrophil extracellular traps (NETs) in all 19 thrombi that were analyzed.ConclusionDiabetes and TICA occlusion were the strongest predictors of atypical clot composition. We also observed a significant association between atypical composition and an increased number of passes. Furthermore, the presence of NETs in all thrombi analyzed, regardless of their composition, indicates inflammatory mechanisms associated with clot formation and consolidation in AIS.